1993
DOI: 10.1073/pnas.90.2.393
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived growth factor (PDGF) in oncogenesis: development of a vascular connective tissue stroma in xenotransplanted human melanoma producing PDGF-BB.

Abstract: Human WM9 melanoma cells, previously shown to be devoid of PDGF expression, were stably transfected with a PDGF-B cDNA under the transcriptional control ofa cytomegalovirus promoter. Northern blot analysis revealed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
124
1
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(131 citation statements)
references
References 43 publications
4
124
1
1
Order By: Relevance
“…2). [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] Several types of cancers, particularly those derived from the ovary, prostate, breast, lung, brain, skin, and bone, express PDGFRa on the malignant cells themselves (Table 1). 22 In 1 experiment in which a human tumor array was probed with a cross-reactive polyclonal rabbit antibody to PDGFRa, PDGFRa expression was noted in approximately 95% of osteosarcomas and chondrosarcomas, in 77% of prostate cancers, in 52% of ovarian cancers, in 65% of breast cancers, and in 51% of lung cancers (N. Loizos, ImClone Systems, unpublished results).…”
Section: The Pdgf/pdgfr Axis In Cellular Signalingmentioning
confidence: 99%
See 2 more Smart Citations
“…2). [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] Several types of cancers, particularly those derived from the ovary, prostate, breast, lung, brain, skin, and bone, express PDGFRa on the malignant cells themselves (Table 1). 22 In 1 experiment in which a human tumor array was probed with a cross-reactive polyclonal rabbit antibody to PDGFRa, PDGFRa expression was noted in approximately 95% of osteosarcomas and chondrosarcomas, in 77% of prostate cancers, in 52% of ovarian cancers, in 65% of breast cancers, and in 51% of lung cancers (N. Loizos, ImClone Systems, unpublished results).…”
Section: The Pdgf/pdgfr Axis In Cellular Signalingmentioning
confidence: 99%
“…59 Investigations in multiple cancer types have highlighted the relevance of both PDGF-activated tumor and supporting stromal cells in facilitating cancer growth and metastasis. [44][45][46][47][48][49][50][51]55,57,60 In some cases, specific autocrine or paracrine mechanisms that contribute to malignant progression have been suggested. In 1 experiment, NIH 3T3 cells were transformed when PDGF-A or PDGF-B gene expression was induced using a transfected promoter.…”
Section: The Pdgf/pdgfr Axis In Cellular Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…8,[12][13][14][15] The mechanisms by which carcinoma cells stimulate stromal connective tissue cells are poorly understood, although data suggesting that transfer of stimulatory factors occurs by a paracrine mechanism have been presented. 14,16 Platelet-derived growth factor (PDGF) induces a stromal response in tumors 17 and induces translation of procollagen type I mRNAs in fibroblasts in which cell spreading has been impaired. 18 Transforming growth factor-␤ (TGF-␤) activates the type I collagen genes, as well as collagen production in vitro and in vivo, 19,20 and has been ascribed to be involved in the formation of tumor desmoplasia, e.g., in scirrhous gastric cancer.…”
mentioning
confidence: 99%
“…In mice, implantation of PDGF B-chain-transfected melanoma cells resulted in increased fibrovascular stroma development relative to untransfected cells. 14 Administration of PDGF B-chain to the chick chorioallantoic membrane resulted in increased numbers of vessels with little inflammation. 15,16 In vitro studies similarly suggested that PDGF B-chain could be proangiogenic under some conditions, and that its target could be either ECs, or vascular smooth muscle cells (SMCs), or both.…”
mentioning
confidence: 99%